Predictors of health-related quality of Life for COVID-19 survivors living in Dhaka, Bangladesh: A repeated Follow-Up after 18 months of their recovery. - Md Utba Rashid; Koustuv Dalal; Md Abdullah Saeed Khan; Umme Kulsum Monisha; Soumik Kha Sagar; Tahmina Zerin Mishu; Mohammad Hayatun Nabi; Mohammad Delwer Hossain Hawlader (Public Library of Science (PLoS), 2024)
The study aimed to explore the key determinants that impact the quality of life (QoL) transformation of those who have recuperated from COVID-19 in the Dhaka metropolis, particularly 18 months post-recovery. RT-PCR confirmed that 1,587 COVID-19 patients from Dhaka were included in the study. The baseline was June - November 2020, subsequently recovered and interviewed 18 months after their initial recovery. The follow-up included 1587 individuals using the WHOQOL-BREF questionnaire. After excluding 18 deaths, 53 refusals, 294 inaccessible participants, and 05 incomplete data entries, we analysed the data of the 1217 respondents. The average physical domain score decreased significantly from baseline to follow-up, whereas a significant increase in average scores has been observed in other domains at the follow-up (p<0.05). GEE equation shows after adjusting for other factors, older age, female gender, higher education, higher family income, hospital admission during COVID-19, and the number of comorbidities were significantly associated with changing individuals' QoL scores. Monthly family income >60000 BDT, being married and having no previous vaccination history are significant in reducing people's QoL scores in the psychological domain. On the other hand, age, employment status, monthly family income, marital status, smoking history, and COVID-19 reinfection were significantly associated with altering an individual's QoL scores in the social domain. The overall QoL of COVID-19 recovered people improved in all domains after 18 months, except the physical realm. Participants' age, employment status, family income, marital status, smoking history, comorbidities, COVID-19 vaccination, and COVID-19 reinfection were responsible for altering people's QoL index.